The "rebound effect" - Ivaldi, Federica (Primerjalna književnost, 2014)
The "rebound effect" is the deep influence of cinema on literature - not at the thematic level, but at the formal and structural one. This essay offers an overview of this theoretical issue, using Italian literary works as examples (e.g., Pasolini, Tabucchi, and Camilleri).
Keywords: Tabucchi, Antonio, 1943-2012; Pasolini, Pier Paolo, 1922-1975; Camilleri, Andrea, 1925-; književnost in film; italijanska književnost; naratologija; narratology; semiotics; semiotika; pripovedne tehnike; intermedialnost